From Polyhalides to Polypseudohalides: Chemistry Based on Cyanogen Bromide. Issue 30 (11th July 2019) - Schmidt, Benjamin; Schröder, Benjamin; Sonnenberg, Karsten; Steinhauer, Simon; Riedel, Sebastian
Abstract: Pseudohalogens are defined as molecular entities that resemble the halogens in their chemistry. While our understanding of polyhalogen chemistry has increased over the last years, research on polypseudohalogen compounds is lacking. The pseudohalogen BrCN possesses a highly pronounced σ‐hole at the bromine side of the molecule, inducing strong halogen bonding. This allows the synthesis and characterization of new polypseudohalogen anions, as shown by the single‐crystal X‐ray diffraction of [PNP][Br(BrCN)] and [PNP][Br(BrCN)3 ]. Both the nearly linear anion [Br(BrCN)] − and the distorted pyramidal anion [Br(BrCN)3 ] − were characterized by Raman spectroscopy and quantum‐chemical calculations. The behavior of the polypseudohalogen compounds in solution and as room‐temperature ionic liquids (RT‐ILs) using the [NBu4 ] + cation was studied by 13 C and 15 N NMR spectroscopy. These types of ILs are capable of dissolving elemental gold and offer themselves as promising compounds in metal recycling. Abstract : Need to solve a "problem"? Strong halogen bonding enables the synthesis and investigation of new polypseudohalogen salts and room‐temperature ionic liquids (ILs) based on cyanogen bromide, such as [Br(BrCN)3 ] − . These reactive ILs are capable of dissolving elemental gold and offer themselves as promising compounds in metal recycling.